Ethical considerations in presymptomatic testing for variant CJD. Issue 11 (3rd November 2005) - Duncan, R E; Delatycki, M B; Collins, S J; Boyd, A; Masters, C L; Savulescu, J
Abstract : Variant Creutzfeldt–Jakob disease (vCJD) is a fatal, transmissible, neurodegenerative disorder for which there is currently no effective treatment. vCJD arose from the zoonotic spread of bovine spongiform encephalopathy. There is now compelling evidence for human to human transmission through blood transfusions from presymptomatic carriers and experts are warning that the real epidemic may be yet to come. Imperatives exist for the development of reliable, non-invasive presymptomatic diagnostic tests. Research into such tests is well advanced. In this article the ethical implications of the availability of these tests are elaborated and comparisons drawn with predictive genetic testing for Huntington's disease and screening for HIV. Paramount to considerations is the issue of whom to test, weighing up respect for personal autonomy against obligations to benefit and protect society. A paradigm is proposed similar to that used for HIV screening but with unique features: compulsory testing of all blood/organ donors and individuals undergoing surgery or invasive procedures who have a significant risk of disease transmission.